Transmutation of Economy and Transference of Status- A Case Study From Tribal Wayanad - Bindu Ramachandran (J. Soc. Sci., 9(1): 1-4 (2004), 2004)
This paper will explore the economic structure of the Adiya community with special reference to their division of labour and changes that has happened in the traditional economy due to socio-cultural factors and how this change in economic relations and roles effect their social status. Agricultural labour forms the basis of material and personal relationships in the social organization of Adiyar , so, any change in this area automatically affect the whole of the system especially the family. In the case of Adiya women, changes in the economic relations and roles has also created changes in the social status of women which is considered as the most striking point